Maternal ratings of temperamental characteristics of healthy premature infants are indistinguishable from those of full-term infants - Keresteš, Gordana (Array, 2005)
Aim. To investigate whether prematurity itself, if not accompanied with serious medical risks, affects early temperamental characteristics, as measured by maternal ratings. Methods. Mothers’ reports of temperamental characteristics of 104 low-risk, healthy premature infants were compared with those from a comparable sample of 120 full-term infants. Mothers completed the Infant Behavior Questionnaire (IBQ) when their infants were 6 or 12 months of age (corrected for prematurity for premature infants). Results. Two groups of infants significantly differed only in one of six IBQ scales, the Activity Level scale, with premature infants being rated by their mothers as more active than full-term infants (ANOVA, p = 0.026). Most of the interactions of prematurity with age and sex were insignificant, as well as the main effects of age and sex. Furthemore, effect sizes (Cohen’ s d) were relatively small, even for statistically significant effects. Correlational analyses performed within the premature sample showed that premature infants’ gestational ages at birth did not significantly correlate with IBQ scales, except with Duration of Orienting scale, on which more premature infants were rated as having shorter periods of orienting (r = 0.21, p = 0.036). Conclusion. Ratings of premature infants’ mothers on five out of six temperament dimensions measured in the study were indistinguishable from those of full-term infants’ mothers. As the study had high power of achieving significant effects of prematurity if they really existed, it can be concluded that prematurity per se, if not accompanied with serious medical problems, did not have profound influence on mothers’ ratings of infant temperament.